Users’ Review on Converged News: Indonesia News Apps Case - Irwansyah, Irwansyah (UI Scholars Hub, 2019)
Review is important for users to adapt, adopt, and accept new mobile applications. The digital and Internet have changed the way of users viewing and reading news. Since news outlet has transformed from print to website, mobile website, and mobile application, the users’ testimony could make them install, use, and be loyal. At the developers’ perspective, the review could make new ways to improve the features of news apps. The news apps that have better features could give better impression to readers. Moreover, news apps could make so much easier for users or readers to keep up with the latest news and information. It makes a lot of interest in the world of news on mobile platforms especially the news outlet that concern on the behaviour of users such as Kompas and Republika. By collecting the reviews and categorizing them with rating appreciation, PACMAD, EMA, TAM, and Nielsen’s Acceptability, this study found that not all categories were relevant and considered perfectly fit in news apps. The new construct has been developed about user appreciation of news apps. The elaboration of measurement gives new implication toward converged news media. The implication of this study would be also discussed and would give theoretical and methodological suggestions for further study